Water salinity evaluation suitability for settlement after ten year tsunami in Banda Aceh, Indonesia - Rusdi, Muhammad; Roosli, Ruhizal; Ahamad, Mohd Sanusi S. (Universitas Malikussaleh, 2014)
Banda Aceh is a residential area that is most severely impacted by the earthquake and tsunami on December 26, 2004. Recently, ten years after the incident, many settlements were rebuilt. As a disaster-prone areas, Banda Aceh would need to be evaluated against the settlement area base on water salinity. The focus of the study centered on the application of geographic information systems in handling spatial data bearing capacity of the land into the concept of the FAO land suitability. To ensure the application works, it requires geospatial analysis compiled based on the salinity of the water variables that can be observed and measured for the residential requirements. The results showed that 86 percent (ordo S) suitable for residential areas and 14 per cent (ordo N) is not suitable.Banda Aceh adalah daerah pemukiman yang paling parah terkena dampak gempa dan tsunami pada 26 Desember 2004. Baru-baru ini, sepuluh tahun setelah kejadian tersebut banyak pemukiman yang dibangun kembali. Sebagai daerah rawan bencana, evaluasi terhadap kadar salinitas pada basis kawasan pemukiman di Banda Aceh perlu dievaluasi. Fokus dari penelitian ini berpusat pada aplikasi sistem informasi geografis dalam penanganan data spasial terhadap dukung data tanah sesuai dengan konsep kesesuaian lahan FAO. Untuk memastikan aplikasi tersebut sesuai, analisis geospasial disusun berdasarkan variabel salinitas air yang diamati dan diukur sebagai persyaratan pembangunan pemukiman. Hasil penelitian menunjukkan bahwa 86 persen (ordo S) cocok untuk daerah pemukiman dan 14 persen (ordo N) adalah tidak cocok.